2019
DOI: 10.1136/bmjgast-2019-000338
|View full text |Cite
|
Sign up to set email alerts
|

Competing mortality risks analysis of prediagnostic lifestyle and dietary factors in colorectal cancer survival: the Norwegian Women and Cancer Study

Abstract: BackgroundIt remains unclear whether or which prediagnostic lifestyle and dietary factors influence colorectal cancer (CRC) survival following diagnosis. This study used competing mortality risks analysis to evaluate the association between these factors and CRC survival.MethodsA total of 96 889 cancer-free participants of the Norwegian Women and Cancer Study completed the study’s baseline questionnaire on lifestyle and dietary factors between 1996 and 2004. Of the 1861 women who subsequently developed CRC, 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A flowchart of the selection process is presented in Figure 1. We excluded 453 publications on exposures other than physical activity, 64 on pre‐diagnosis‐only exposures, 43–106 seven on a mixture of pre‐and post‐diagnosis exposures, 107–113 and one where the outcome was colorectal polyps 114 . Overall, 28 publications met the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of the selection process is presented in Figure 1. We excluded 453 publications on exposures other than physical activity, 64 on pre‐diagnosis‐only exposures, 43–106 seven on a mixture of pre‐and post‐diagnosis exposures, 107–113 and one where the outcome was colorectal polyps 114 . Overall, 28 publications met the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Lower 25OHD level is strongly associated with CRC survival in observational data, 14 , 16 , 17 providing a strong rationale for supplementation trials in cancer patients with survival outcomes as the defined endpoint yet observational studies of vitamin D supplementation or intake and survival do not provide consistent evidence of benefit from vitamin D. A Norwegian study recently reported better CRC survival in incident CRC cases with pre-diagnostic vitamin D intake of >400 IU/day (HR = 0.75; 95% CI: 0.61–0.92). 41 Similarly, the Cancer Prevention Study-II reported a trend towards greater OS in those with higher total or dietary vitamin D intake (HR = 0.88; 95% CI: 0.57–1.35 and HR = 0.90; 95% CI: 0.67–1.21), yet even in quartile four, the intake was low (~>245 IU/day). 42 Jeffreys et al 43 reported a non-significant reduction in mortality after CRC diagnosis in women who had been prescribed vitamin D supplementation in the 5 years preceding CRC diagnosis (13% of 4122 cases prescribed supplements; HR = 0.90; 95% CI: 0.78–1.04), yet some other studies have found no benefit from low-dose supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…We used one of the two most recent measurements before self-reported FM or the end of follow-up, whichever came first. Body mass index (BMI) was calculated as weight in kilograms divided by height in meters squared and categorized as underweight (< 18.5 kg/m 2 ), normal weight (BMI 18.5–24.9 kg/m 2 ), overweight (BMI 25–29.9 kg/m 2 ), and obese (BMI ≥ 30 kg/m 2 ) [ 31 34 ]. Physical activity (PA) level was measured on a validated 10-point ordinal scale [ 28 ] and categorized as 1–2 very low; 3–4 low; 5–6 moderate; 7–8 high; 9–10 very high.…”
Section: Methodsmentioning
confidence: 99%